The Canadian Manufacturing Sector, 2002-2008: Why Is It Called Dutch Disease? - Stephen Gordon (The School of Public Policy Publications, 2013)
High-profile complaints about so-called Dutch disease have led many to question if industry in some parts of the country is suffering due to the success of the natural resources sector in others. This paper considers changes in manufacturing employment from 2002- 2008, a time of increased commodity prices. At first glance, the figures appear alarming — Canada shed 328,000 manufacturing jobs during that period — but the decline wasn’t entirely commodity-driven. Canada is the sole G-7 country in which manufacturing is on par with what it was 40 years ago; manufacturing employment rose in the decade prior to the decline thanks to government austerity, which spurred monetary easing, making industry more export-competitive. Much of the contraction from 2002-2008 was a natural reaction to this unsustainable situation. Higher commodity prices in the same period actually had a benign — if not positive — effect on Canada’s manufacturing industry, notwithstanding the fall in employment. The manufacturing jobs that were lost were typically low paying, and were offset by the creation of betterpaying employment in other sectors. The available data on gross employment flows suggest that the disruptions associated with the shift of employment out of manufacturing were surprisingly small. The reduction in employment was largely achieved through attrition; layoff rates held steady while hiring rates fell. Moreover, the data are not consistent with fears that the manufacturing sector was hollowed out. Research and development activities held steady and investment in new technology continued to grow, leaving the manufacturing sector healthier in 2008 than it was in 2002.